The Muqaddimah of Qanun Asasi by KH. Hasyim Asy’ari as an Epistemological Framework for Aswaja An-Nahdliyah Cadre Formation - Ahmad Muzakki Al Mahbubi; Imron Arifin (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2024)
This study examines Qanun Asasi of KH. Hasyim Asy’ari as the epistemological framework of Aswaja (Ahlussunnah wal Jama’ah) cadre formation within Nahdlatul Ulama. Unlike previous studies that position Qanun Asasi merely as a historical or organizational document, this research conceptualizes it as an integrated architecture of knowledge shaping the cadre system. Employing a textual-historical analysis of the official edition of Qanun Asasi Nahdlatul Ulama and engaging Islamic epistemology and critical theory perspectives, the findings reveal that the triadic structure of aqidah–fiqh–tasawwuf forms ontological, methodological, and ethical foundations. These foundations systematically generate the operational principles of tawassuth (moderation), tawazun (balance), tasamuh (tolerance), and i‘tidal (justice). These principles are not merely normative slogans but epistemic consequences of the integration of theology, law, and spirituality. This epistemological structure is translated into a cadre formation model integrating cognitive, affective, and social praxis dimensions. The study concludes that religious moderation within Nahdlatul Ulama is rooted in a consistent epistemological construction since 1926 and retains transformative relevance in contemporary plural societies.